Modern views on etiology and pathogenesis of Parkinson's disease - А.V. Kutsak; N. M. Buchakchyiska (Zaporožskij Medicinskij Žurnal)
Aim. To analyze the specialized scientific literature for data generalization concerning current views on etiology and pathogenesis of Parkinson's disease (PD).